TRAM BREAST RETAIL RECONSTRUCTION: AN ANALYSIS IN THE LATE POSTOPERATIVE - Andrade, Thainá Sobral de; Figueiredo, Yasmin Alves da Cruz; Felzemburgh, Victor Araújo; Carneiro, Pedro Paulo Oliveira (Mastology, 2021)
In Brazil, breast cancer represents the second most incident cancer among women and is the major cause of death from malignant neoplasms in females. Therefore, the treatment of this pathology needs to be studied in its various aspects, one of which is aesthetic care in breast reconstruction. Objectives: To evaluate the late result of breast reconstruction by TRAM (transverse rectus abdominis muscle flap), in addition to comparing the assessment instruments in the postoperative period. Postoperative photographs of 13 patients who underwent breast reconstruction by TRAM at Hospital Santo Antônio in Salvador, BA, in the period 2012 and 2018 were analyzed. This is a cross-sectional observational study, with aesthetic evaluation performed using two instruments. Results: In general, patients have satisfactory results in the two assessment tools. Of the patients studied, 61.5% had results within the parameters established by Mallucci, whereas evaluating the domains of Garbay’s criteria, the best mean result was related to the volume domain and the worst to the scar. Conclusion: The instruments proved to be appropriate for evaluating the patients in the study. The subjective analysis among the evaluators proved to be similar. The instrument used in morphometric analysis showed that the studied group of patients approached the parameter established as ideal.